2007
DOI: 10.1111/j.1742-7843.2007.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tetrahydrocurcumin on Hepatic and Renal Functional Markers and Protein Levels in Experimental Type 2 Diabetic Rats

Abstract: Curcumin is the most active component of turmeric. It is believed that curcumin is a potent antioxidant and anti-inflammatory agent. Tetrahydrocurcumin is one of the major metabolites of curcumin that exhibits many of the same physiologic and pharmacological activities as curcumin and in some systems may exert greater antioxidant activity than curcumin. Oral administration of tetrahydrocurcumin at 80 mg/kg body weight to diabetic rats for 45 days resulted in a significant reduction in blood glucose and signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 28 publications
3
61
0
Order By: Relevance
“…8). Murugan and Pari (2007) suggested that curcumin and tetrahydrocurcumin safeguard against kidney dysfunction through the inhibition of the synthesis of non-enzymatic antioxidants in diabetic rats. Additionally, curcumin induces apoptotic cell death by cycle arrest in the S and G2/M phases (Sharma et al, 2005;Ye et al, 2012) and may help to remove damaged cells, e.g.…”
Section: Curcumin Extend the Apian Resistance And Life Span Resultsmentioning
confidence: 99%
“…8). Murugan and Pari (2007) suggested that curcumin and tetrahydrocurcumin safeguard against kidney dysfunction through the inhibition of the synthesis of non-enzymatic antioxidants in diabetic rats. Additionally, curcumin induces apoptotic cell death by cycle arrest in the S and G2/M phases (Sharma et al, 2005;Ye et al, 2012) and may help to remove damaged cells, e.g.…”
Section: Curcumin Extend the Apian Resistance And Life Span Resultsmentioning
confidence: 99%
“…Its oral administration has been shown to prevent body weight loss, reduce the levels of haemoglobin (Hb), glucose, and glycosylated hemoglobin (HbA1C) in blood (Arun and Nalini, 2002). The same route of administration has also been reported to improve insulin sensitivity (Murugan and Pari, 2007b). In an STZ-induced diabetic rat model (Chougala et al, 2012), it was observed that dietary curcumin (0.5% in diet) was effective in reducing the increased levels of fasting blood glucose, urine sugar, and urine volume.…”
Section: Effect Of Curcumin On Diabetesmentioning
confidence: 95%
“…THC was more active than curcumin in modulating renal and hepatic functional markers in diabetic rats [72] •THC was more active than curcumin in modulating erythrocyte TBARS in diabetic rats [59].…”
Section: Studies Showing Thc To Be More Active Than Curcuminmentioning
confidence: 96%
“…Murugan and Pari [72] also examined the lipid profile and lipid peroxidation in rats with streptozotocin-nicotinamide-induced diabetes after exposure to curcumin. They found that both curcumin and THC induced a significant reduction in blood glucose and a significant increase in plasma insulin in diabetic rats; curcumin and THC also caused a significant reduction in lipid peroxidation (TBARS and hydroperoxides) and lipids (cholesterol, triglycerides, free fatty acids, and phospholipids) in serum and tissues.…”
Section: Antidiabetic Effectsmentioning
confidence: 99%
See 1 more Smart Citation